The Empirical Analysis of the Impact of Bank Capital Regulations on Operating Efficiency - Josephat Lotto (International Journal of Financial Studies, 2018)
This paper principally aims at examining the impact of capital requirements regulation on bank operating efficiency in Tanzania. The study employs bank level data for the period between 2009 and 2015. The findings show a positive and significant relationship between capital ratio and bank operating efficiency. This shows that commercial banks in Tanzania with more stringent capital regulations are more operationally efficient. This relationship proposes that capital adequacy does not only strengthen financial stability by providing a larger capital cushion but also improves bank operating efficiency by preventing a moral hazard problem between shareholders and debt-holders. This result may also imply that the increased regulations on capital requirements influence the bank’s decision to revisit their internal operations strategy in terms of strong corporate governance, risk assessment methods, credit evaluation procedures, employment of more qualified staffs, and enhanced internal control procedures. Another key finding is an inverse relationship between non-performing Loans (credit risk) and bank operating efficiency. The implication of this relationship may simply mean that the bank’s total loan and advances in combination with total deposit either due from customers or from other banks are of little importance in determining the operational efficiency of banks. This probably implies that the amount of money banks loan out is too excessive, which would attract a greater chance of default. The paper lays down some recommendations: first, banks in Tanzania are advised to invest in more advanced technological innovations to reduce the staff costs and other operating expenses to increase their operational efficiency; and, second, bank management is also advised to be more careful in the loan screening process to reduce the incidence of non-performing loans.